2015
DOI: 10.1080/02640414.2015.1068436
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Myotest® for measuring running stride kinematics

Abstract: Accelerometer-based systems are often used to quantify human movement. This study's aim was to assess the reliability and validity of the Myotest® accelerometer-based system for measuring running stride kinematics. Twenty habitual runners ran two 60 m trials at 12, 15, 18 and 21 km·h(-1). Contact time, aerial time and step frequency parameters from six consecutive running steps of each trial were extracted using Myotest® data. Between-trial reproducibility of measures was determined by comparing kinematic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 28 publications
1
68
0
5
Order By: Relevance
“…Jump height was measured by a Myotest device (Myotest, Sion, Switzerland), which is based on 3D acceleration, is designed for commercial use, and is worn at the waist. The validity and reliability of the Myotest device have been recently verified (Casartelli, Muller, & Maffiuletti, 2010;Castagna, 2013;Comstock et al, 2011;Dinu et al, 2011;Gindre et al, 2016;Houel, Faury, & Seyfried, 2013;Choukou, Laffaye, & Taiar, 2013).…”
Section: Methodsmentioning
confidence: 93%
“…Jump height was measured by a Myotest device (Myotest, Sion, Switzerland), which is based on 3D acceleration, is designed for commercial use, and is worn at the waist. The validity and reliability of the Myotest device have been recently verified (Casartelli, Muller, & Maffiuletti, 2010;Castagna, 2013;Comstock et al, 2011;Dinu et al, 2011;Gindre et al, 2016;Houel, Faury, & Seyfried, 2013;Choukou, Laffaye, & Taiar, 2013).…”
Section: Methodsmentioning
confidence: 93%
“…1, while the peak velocities can be seen in Fig. 2 (for a heel striker) and Myotest Run is a portable device that uses triaxial accelerometry to quantify different stride parameters including contact time [3,5]. It was placed on the belt of the runner.…”
Section: Measurementsmentioning
confidence: 99%
“…However, although highly expensive treadmills and long running tracks with force platforms already exist, if more than one event needs to be measured, it is necessary to use alternative methods of determining stride phase durations. In this way, new field tools based on optical detection (OptoGait) and accelerometer systems (Myotest Run) represent good alternatives that quickly provide feedback on running gait parameters [2][3][4][5]. Indeed, these two tools are usually used for the measure of several parameters of the stride, including contact time [6].…”
mentioning
confidence: 99%
“…Regarding the accuracy of a step counter using 3-axial acceleration data, Koizumi et al (5) reported that there was a significant difference between the real and the measured values at the 5% significance level in a 120 m/min run, and Gindre et al (6) reported a similar finding. We note here that an accurate analysis of a step counter has not been established.…”
Section: Introductionmentioning
confidence: 97%